2023
DOI: 10.1021/acs.joc.2c02658
|View full text |Cite
|
Sign up to set email alerts
|

Rapid C–H Transformation: Addition of Diarylmethanes to Imines in Seconds by Catalytic Use of Base

Abstract: The addition of diarylmethanes or methylarenes via activation of benzylic C(sp 3 )−H bonds to N-aryl imines proceeds under catalysis by alkali hexamethyldisilazide (HMDS) base to give N-(1,2,2-triarylethyl)anilines or N-(1,2-diarylethyl)anilines, respectively. In the presence of 10 mol % of LiHMDS at room temperature, the diarylmethane addition equilibrates within 20−30 s and is driven to near completion by cooling the reaction mixture to −25 °C, providing N-(1,2,2-triarylethyl)aniline in a >90% yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Fluorine‐containing products 3 apa and 3 aea displayed lower yields due to side reactions. Likewise, ring‐methylated ( 2 ba – 2 da ), ‐halogenated ( 2 qa , 2 ra ), or heterocyclic imines suffered from base‐induced self‐polymerization [18] and gave the respective products 3 xa in low yield ( cf . Scheme S1) [39]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fluorine‐containing products 3 apa and 3 aea displayed lower yields due to side reactions. Likewise, ring‐methylated ( 2 ba – 2 da ), ‐halogenated ( 2 qa , 2 ra ), or heterocyclic imines suffered from base‐induced self‐polymerization [18] and gave the respective products 3 xa in low yield ( cf . Scheme S1) [39]…”
Section: Resultsmentioning
confidence: 99%
“…[38] We have recently described base-catalyzed additions of diarylmethanes to imines and found that methylarenes likewise add to imines after suitable modification of the reaction conditions (Scheme 1c). [18] This led us to propose a synthesis of indolines by a transition-metal-free, but base-mediated process by combining the Mao/Walsh approach of benzylic C(sp 3 )À H bond activation in ortho-fluorinated methylarenes with 1,2addition to imines, with an ensuing defluorinative S N Arcyclization of an alkali amide intermediate (Scheme 1d). A related precedent by García Ruano et al condensed orthoalkyl(4-tolylsulfinyl)benzenes with perfluoroalkyl imines (Scheme 1e), but was limited by the fairly specific reaction partners.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With these advantages very recently, Hintermann and co-workers disclosed the synthesis of N-(1,2-diarylethyl) aniline 5 mediated by KN(SiMe 3 ) 2 or NaN(SiMe 3 ) 2 (Scheme 5). [27] Unlike the above-mentioned reports, here Hintermann and co-workers directly employed the imines instead of aldehydes (in situ generated aldimines under MN(SiMe 3 ) 2 conditions). They observed that the KN(SiMe 3 ) 2 with bigger cation K + mediated the reaction with 1 equiv.…”
Section: Aminobenzylationmentioning
confidence: 99%